Unique Rational Explanations on Resurrection and the Hereafter from the Man of the Millennium - Hüseyin Çaksen; Khalid Hussain Mir (al-Afkar, Journal For Islamic Studies, 2025)
"Unique Rational Explanations on Resurrection and the Hereafter from the Man of the Millennium" by Bediüzzaman Said Nursi presents a profound exploration of resurrection and the afterlife through the lens of Islamic theology. This review delves into the significance of Nursi's work, highlighting its logical rigor, theological insights, and relevance across various disciplines. Drawing inspiration from the Quran, Nursi's treatise offers compelling arguments and metaphors to elucidate the core tenets of Islamic eschatology. The review emphasizes the book's contribution to fostering a rational understanding of these timeless subjects, making it essential reading for scholars, practitioners, and seekers interested in delving deeper into matters of faith, philosophy, and psychology.